2021
DOI: 10.52587/jems020203
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Determinants of Economic Growth: Evidence From Pakistan

Abstract: This study aims to analyze the impact of different deriving forces like trade balance, capital, inflation rate, exchange rate and government fiscal measures on economic growth of Pakistan during the period 1977 to 2019. The empirical results are tested through ARDL co-integration method which indicates that capital, inflation rate, exchange rate and tax revenues have significant long term and short term relationship with economic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Findings from the study revealed that in ation, exchange rate and money supply impacted Indonesia's GDP. Waheed and David (2021) showed using the ARDL procedure that in ation and exchange rates, capital, and tax receipts determine GDP growth for Pakistan. By applying a multimodal panel procedure for 34 African countries, Batrancea et al (2021) showed that exports, imports, gross domestic savings, and gross capital formation are crucial determinants of GDP.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Findings from the study revealed that in ation, exchange rate and money supply impacted Indonesia's GDP. Waheed and David (2021) showed using the ARDL procedure that in ation and exchange rates, capital, and tax receipts determine GDP growth for Pakistan. By applying a multimodal panel procedure for 34 African countries, Batrancea et al (2021) showed that exports, imports, gross domestic savings, and gross capital formation are crucial determinants of GDP.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Findings from the study revealed that inflation, exchange rate and money supply impacted Indonesia's GDP. Waheed and David (2021) showed using the ARDL procedure that inflation and exchange rates, capital, and tax receipts determine GDP growth for Pakistan. By applying a multimodal panel procedure for 34 African countries, Batrancea et al (2021) showed that exports, imports, gross domestic savings, and gross capital formation are crucial determinants of GDP.…”
Section: Empirical Reviewmentioning
confidence: 99%